Analysis of a Recent Biofilter Model for Toluene Biodegradation - Qasim, Muhammad (2013)
This paper investigates and provides a critical analysis of the toluene biofilter model developed by Li and De Visscher. The model simulation results have been reproduced and compared with several sets of experimental data from literature. Three different model variations are considered: model with no substrate inhibition, with substrate inhibition, and with air flow rate modification. A sensitivity analysis has been performed on model to study the effect of important parameters on the removal efficiency. Model limitations and improvements have been highlighted.